Report of the Internship Programme in Leiden University under the guidance of Prof. Dr. C.A. Van Peursen on the Process Philosophy - Supadjar, Damardjati (Fakultas Filsafat UGM, 1990)
In answering the perennial philosophical problem, the fhilosophy of Procces has e synthetic approach, not to choose either. Or, but combine "both.. and.." Both"one" and "many", "permanence" and "fluk", are aspects of teh Reality. A.N. Whitehead, as one of the Procces Phylosopher, saw that we have an oerganic and creative universe: that is why the Philosophy of process is also called The Philosophy of organism. The nation that underlies all and everthing is creativity: and Go is its primordial accident. Go is the Beginning and the end. He is not before everything, but within it. The dialectic of idealims and heterogenius dialectic.